Hasan Minhaj’s Spontaneous Conversational Humor in Patriot Act - Fakhriani, Zummia (English Literature Study Program, 2023)
Grice's maxim of conversation becomes the main condition for a complete and ideal conversation. Spontaneous conversational humor is used in communicating with others, in light conversations with relatives, and in a broader public space, such as television shows and radio broadcasts. This linguistic phenomenon is often used as a speaker strategy in criticizing an action of an individual that is distorted but narrated in the form of humor that invites the audience's laughter. The researcher analysed Hasan Minhaj’s and his audience's spontaneous conversational humor in this study. Methodologically, the researcher adopted Grice's pragmatics study on the Theory of Cooperative Principle (1975), which aimed to make conversations cooperative. The researcher collected the data from Hasan Minhaj and his audience's utterances from September 2, 2019, to November 11, 2019. 21 data in the form of spoken transcripts containing spontaneous conversational humor, analysed by Martin's theory of spontaneous humor categorization (2007), which also contained non-observances (floating) based on the principle of conversation proposed by Grice (1975). The results showed that Hasan Minhaj deliberately and spontaneously expressed humorous conversations on his TV show